Ict Support Assessment in Primary School Teaching and Learning Through Ahp - Oddershede-Herrera, A; Donoso-Oyarzun, J (Elsevier B.V., 2015)
The aim of this study is to analyse the importance of Information and Communication Technology (ICT) support at primary school. Applying the analytic hierarchy process (AHP) a decision model is proposed to reveal the effect of ICT system support in teaching and learning process performance at primary school. A case study is pursued involving private and state schools at a zone in the Metropolitan Region in Chile. First-hand data is gathered comprising different agents involved with education, primary schools and with academic experience. The outcome indicate the key aspects showing those schools who assigned priority to the ICT support had better results in the teaching and learning process. © 2015 The Authors. Published by Elsevier B.V.